(3TQM GdCLQhejIs - (3TgGH GdOjf CHh GdYHGS CMeO Hf CMeO GdQedi GdCfUGQj GdTGaYjs; (3GHf BoLoqQhe, eMeO Hf eMeO Hf OGhO GdUfgGLj, CHh YHO Gddg,J (B723 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Gdedc GdYdGe CeG HYO agPG JYdjb Ydi ebOeg GdTgjQ HGHf BLQhe HSe Gddg GdQMef dGQMje GdHGA eJYdbI HeMPha hGdGSe eTJb ef GdSeh s
(3BNQgG (B:s
(3hgPg GdUaI KdGKI CfhGY CeScaGYd cgPG VGQH RjO GdBf Ch ZOkG hGSe GdeaYhd dgPG eYehQ GdOGQ GdBf Ch ZOkG hGdUaI GdeTHgI HGSe GdaGYd cgPG QLd MSf GdhLg CMSf Gddg YGbHJfG HeMeO hBdg hGdMeO ddg hMOg hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HBNQgG Jedc HGSe Ydi Hf YHO Gddgs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdfMhs